Individuals with numerical and structural variations of sex chromosomes: interdisciplinary management with focus on fertility potential - Juul, Anders; Gravholt, Claus H.; De Vos, Michel; Koledova, Ekaterina; Cools, Martine (Frontiers in Endocrinology, 2023)
Diagnosis and management of individuals who have differences of sex development (DSD) due to numerical or structural variations of sex chromosomes (NSVSC) remains challenging. Girls who have Turner syndrome (45X) may present with varying phenotypic features, from classical/severe to minor, and some remain undiagnosed. Boys and girls who have 45,X/46,XY chromosomal mosaicism may have Turner syndrome-like features and short stature; therefore, unexplained short stature during childhood requires karyotype analysis in both sexes, particularly if characteristic features or atypical genitalia are present. Many individuals with Klinefelter syndrome (47XXY) remain undiagnosed or are only diagnosed as adults due to fertility problems. Newborn screening by heel prick tests could potentially identify sex chromosome variations but would have ethical and financial implications, and in-depth cost-benefit analyses are needed before nationwide screening can be introduced. Most individuals who have NSVSC have lifelong co-morbidities and healthcare should be holistic, personalized and centralized, with a focus on information, psychosocial support and shared decision-making. Fertility potential should be assessed individually and discussed at an appropriate age. Oocyte or ovarian tissue cryopreservation is possible in some women who have Turner syndrome and live births have been reported following assisted reproductive technology (ART). Testicular sperm cell extraction (TESE) is possible in some men who have 45,X/46,XY mosaicism, but there is no established protocol and no reported fathering of children. Some men with Klinefelter syndrome can now father a child following TESE and ART, with multiple reports of healthy live births. Children who have NSVSC, their parents and DSD team members need to address possibilities and ethical questions relating to potential fertility preservation, with guidelines and international studies still needed.